Tailoring conductive filaments by electroforming polarity in Memristive based TiO2 junctions - Ghenzi, Néstor (2014)
We probe the resistive switching response of Au/TiO2/Cu junctions, on samples initialized using both polarities electroforming. A conductive path is formed in both cases: a copper metallic filament for negative electroforming and a titanium dioxide possibly Magneli phase based filament for the positive case. We measured the resistance response of formed samples and studied their remanent resistance states. Bi (tri) stable resistance states were obtained for negative (positive) electroformed samples. The temperature dependence of the resistance discloses the underlying different nature of the associated filaments. In addition, we performed ab initio calculations to estimate the observed electroforming threshold voltages.